TEMPUS EDAX RERUM,: aneb o minulosti a současnosti vojvodovských Čechů - Penčev, Vladimir (Lidé města, 2003)
The study examines the history of a complex search for a new home, underwent in the 1890s by a group of Banat Czechs from the locality Svatá Helena in order to maintain the integrity of its religious community. These "Free reformed Protestants," who adopted a severe, ascetic way of life, settled in the village of Vojvodovo (Orjachovicko) at the end of the 19th and beginning of the 20th centuries. It gives an account of subsequent migration movements which came about in the 1920s and 1930s as well as re-settlement waves to Czechoslovakia after 1946, which actually closed the history of the Czech Vojvodovo. Serious attention is devoted to the description of social organisation and way of life of the Vojvodovo Czechs from 1900 to 1945, which were developed under the influence of a singular, voluntary religious code, transmitted through exchange of generations.